Amorphizing of Au Nanoparticles by CeOx–RGO Hybrid Support towards Highly Efficient Electrocatalyst for N2 Reduction under Ambient Conditions. Issue 33 (6th July 2017) - Li, Si‐Jia; Bao, Di; Shi, Miao‐Miao; Wulan, Ba‐Ri; Yan, Jun‐Min; Jiang, Qing
Abstract : Ammonia synthesis is one of the most kinetically complex and energetically challenging chemical processes in industry and has used the Harber–Bosch catalyst for over a century, which is processed under both harsh pressure (150–350 atm) and hightemperature (623–823 K), wherein the energy and capital intensive Harber–Bosch process has a huge energy cost accounting for about 1%–3% of human's energy consumption. Therefore, there has been a rough and vigorous exploration to find an environmentally benign alternative process. As the amorphous material is in a metastable state and has many "dangling bonds", it is more active than the crystallized one. In this paper, CeO x ‐induced amorphization of Au nanoparticles anchored on reduced graphite oxide (a‐Au/CeO x –RGO) has been achieved by a facile coreduction method under ambient atmosphere. As a proof‐of‐concept experiment, a‐Au/CeO x –RGO hybrid catalyst containing the low noble metal (Au loading is 1.31 wt%) achieves a high Faradaic efficiency (10.10%) and ammonia yield (8.3 μg h −1 mg −1 cat . ) at −0.2 V versus RHE, which is significantly higher than that of the crystalline counterpart (c‐Au/RGO), and even comparable to the yields and efficiencies under harsh temperatures and/or pressures. Abstract : CeOx ‐induced amorphization of Au nanoparticles anchored on reduced graphite oxide (a‐Au/CeOx –RGO) as a heterogeneous electrocatalyst shows excellent catalytic activity for electrochemical N2 reduction reaction with high Faradic efficiency (10.10%) and ammonia yield (8.3 μg h ‐1 mg ‐1 cat . )